Aplikasi Jaring Amal Sebagai Media Promosi Bagi Penyandang Difabel - Darwas, Rahmadini; Putri, Yessy Prima; Alfawwazy, Dzaky (JOSTECH: Journal of Science and Technology, 2021)
Having physical limitations is not a barrier for people with diffable to continue working and produce creative work and be able to contribute to society. The creative work has not been maximally introduced to the community, only through word of mouth promotion of the surrounding community. This study aims to promote the work of people with diffable so that it is more valuable. The method used in software development in this study is the wa-terfall method, while the tools used in the design of this application are unified modeling language and this application is built using a web-based programming language. This re-search results in an online shopping application while doing charity (net of charity) that makes it easy to do promotions and transactions for people based on humanity